Invasion of glioma cells through confined space requires membrane tension regulation and mechano-electrical coupling via Plexin-B2 - Chrystian Junqueira Alves; Theodore Hannah; Sita Sadia; Christy Kolsteeg; Angela Dixon; Robert J. Wiener; Ha Nguyen; Murray J. Tipping; Júlia Silva Ladeira; Paula Fernandes da Costa Franklin; Nathália de Paula Dutra de Nigro; Rodrigo Alves Dias; et al. (Nature Communications)
Abstract Glioblastoma (GBM) is a malignant brain tumor with diffuse infiltration. Here, we demonstrate how GBM cells usurp guidance receptor Plexin-B2 for confined migration through restricted space. Using live-cell imaging to track GBM cells negotiating microchannels, we reveal endocytic vesicle accumulation at cell front and filamentous actin assembly at cell rear in a polarized manner. These processes are interconnected and require Plexin-B2 signaling. We further show that Plexin-B2 governs membrane tension and other membrane features such as endocytosis, phospholipid composition, and inner leaflet surface charge, thus providing biophysical mechanisms by which Plexin-B2 promotes GBM invasion. Together, our studies unveil how GBM cells regulate membrane tension and mechano-electrical coupling to adapt to physical constraints and achieve polarized confined migration.